Implementation of Stunting Handling Policy in Palu City - Puspita, Diah; Mangngasing, Nasir; Nuraisyah, Nuraisyah (International Journal of Social Science, Education, Communication and Economics, 2024)
This research aims to describe, analyze, and interpret the process of implementing policies for handling stunting and identifying factors that support and hinder the handling of stunting in Palu City. The research method used was descriptive research with a qualitative approach, with sampling using the Purposive Sampling method, with a total of 7 informants. The theory used is the Van Meter and Van Horn Theory. The research results show that regarding measures and objectives, there are already standards in implementing policies, but there are still implementers who do not understand the standards, goals, and targets in implementing policies properly. Human resources at the lower level are still lacking both in terms of quantity and quality, the availability of budget resources is quite good. Characteristics of implementing organizations, there are still implementers who do not have SOPs in implementing policies. The attitude of the implementers and the response of the implementers in implementing the policy are quite good, but the public's understanding of stunting prevention is still lacking. Communication and coordination are still lacking, because there are still activities that are not on target in their implementation. The conditions of the social environment, economic environment, and political environment in the city of Palu do not fully support the success of accelerated integrated stunting prevention policies.